2021
DOI: 10.1111/joim.13262
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term neuropsychiatric outcomes and quality of life in COVID‐19 survivors

Abstract: Background The general medical impacts of coronavirus (COVID‐19) are increasingly appreciated. However, its impact on neurocognitive, psychiatric health and quality of life (QoL) in survivors after the acute phase is poorly understood. We aimed to evaluate neurocognitive function, psychiatric symptoms and QoL in COVID‐19 survivors shortly after hospital discharge. Methods This was a cross‐sectional analysis of a prospective study of hospitalized COVID‐19 survivors follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
144
4
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 40 publications
10
144
4
4
Order By: Relevance
“…Among 9751 total participants, 5266 (54.0%) were male; 30 studies 9 , 10 , 11 , 12 , 13 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 51 , 52 reported mean or median ages younger than 60 years, and 14 studies 9 , 11 , 12 , 13 , 24 , 26 , 27 , 33 , 34 , 35 , 36 , 45 , 46 , 52 reported mean or median ages of 50 years or younger ( Table 1 ). Twenty-four studies 9 , 11 , 12 , 13 , 15 , 19 , 20 , 22 , 23 , 24 , 26 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 9751 total participants, 5266 (54.0%) were male; 30 studies 9 , 10 , 11 , 12 , 13 , 15 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 40 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 51 , 52 reported mean or median ages younger than 60 years, and 14 studies 9 , 11 , 12 , 13 , 24 , 26 , 27 , 33 , 34 , 35 , 36 , 45 , 46 , 52 reported mean or median ages of 50 years or younger ( Table 1 ). Twenty-four studies 9 , 11 , 12 , 13 , 15 , 19 , 20 , 22 , 23 , 24 , 26 ,…”
Section: Resultsmentioning
confidence: 99%
“…Time zero definitions and lengths of follow-up varied substantially across studies, with very few studies using identical approaches to defining time zero, follow-up, and reporting. Time zero was defined as diagnosis or symptom onset in 16 studies, 10 , 11 , 22 , 24 , 27 , 31 , 33 , 35 , 37 , 39 , 40 , 41 , 45 , 47 , 48 , 50 hospital admission in 4 studies, 9 , 18 , 25 , 46 hospital discharge in 23 studies, 12 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 26 , 28 , 29 , 30 , 32 , 36 , 38 , 42 , 43 , 45 , 48 , 49 , 51 , 52 and recovery from acute illness in 4 studies. 8 , 13 , 34 , 44 Two studies used different time zero definitions for outpatients vs inpatients within the same study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a general cognitive decay, i.e., deficit in attention and calculation, short-term memory, constructional apraxia, and written language, was also observed during up to 6 months of follow-up ( 61 ). At 2 months of follow-up 58.7% of 179 mild-to-severe COVID-19 patients presented a moderate neurocognitive decline while 39.1% of patients also showed psychiatric morbidity ( 56 ). At a longer follow-up of 6 months, Pilotto et al, analyzing retrospectively 165 moderate-to-severe COVID-19 patients, showed that these long-term symptoms persisted in about 37% of patients ( 61 ).…”
Section: Resultsmentioning
confidence: 99%